Mapping in the region of Danforth's short tail and the localization of tail length modifiers. - Alfred, J B; Rance, K; Taylor, B A; Phillips, S J; Abbott, C M; Jackson, I J (Genome Research, 1997)
We have used an interspecific backcross to generate a detailed genetic map around the mouse tail and kidney developmental mutation Danforth's short tail (Sd). The map includes 14 simple sequence repeat (SSR) markers and four genes in a 5-cM region encompassing Sd. In addition we have used a DNA pooling approach to carry out a genome scan to localize quantitative trait loci (QTL) that modify the tail length of Sd progeny of the backcross. This has allowed us to identify a major QTL on chromosome 10 in the region of nodal and three other putative tail length QTL on chromosomes 1, 9, and 18.